2017
DOI: 10.1007/s00204-017-2116-5
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific risk assessment of PFHxS using a physiologically based pharmacokinetic model

Abstract: Perfluorohexanesulfonate (PFHxS), which belongs to the group of perfluoroalkyl and polyfluoroalkyl substances (PFASs), has been extensively used in industry and subsequently detected in the environment. Its use may be problematic, as PFHxS is known to induce neuronal cell death, and has been associated with early onset menopause in women and with attention deficit/hyperactivity disorder. Due to these impending issues, the aim of this study is to develop and evaluate a physiologically based pharmacokinetic (PBP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Kim et al. () developed a model for simulating the kinetics of PFHxS in male and female rats. The model includes compartments representing plasma (including a bound and free fraction), kidney and renal glomerular filtrate, gastrointestinal tract as absorption site, liver (taking into consideration enterohepatic circulation), brain, heart, lung and the rest of the body.…”
Section: Assessmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim et al. () developed a model for simulating the kinetics of PFHxS in male and female rats. The model includes compartments representing plasma (including a bound and free fraction), kidney and renal glomerular filtrate, gastrointestinal tract as absorption site, liver (taking into consideration enterohepatic circulation), brain, heart, lung and the rest of the body.…”
Section: Assessmentmentioning
confidence: 99%
“…The rat PBPK model was extrapolated to humans, considering the interspecies physiological parameters, on the basis of the same allometric equation described by Kim et al. (), as reported above.…”
Section: Assessmentmentioning
confidence: 99%
“…It was demonstrated that the elimination ratio of individual compounds belonging to the group of PFASs depended on the type of absorbed compound, species of the exposed individual as well as its age and sex. A general tendency has indicated a more rapid elimination of PFASs by females [23,100,101], which may be explained by differences in renal activity, including differences in activity of proteins transporting organic anions [102]. Furthermore, rapid elimination of PFASs by women may be partially explained by PFASs offloading into menstrual blood, as well as in childbirth [103].…”
Section: Excretionmentioning
confidence: 99%
“…Since current toxicity data of PFHxS and PFBS indicate that they are less toxic than PFOS and PFOA, it was expected that they should have higher PNEC than PFOS [48][49][50][51][52] . The measured concentration of PFHxS and PFBuS in water and sediment were even lower than the PNEC of PFOS.…”
Section: Concentraɵonmentioning
confidence: 99%